Cerebral small vessel disease and incident parkinsonism: The RUN DMC study. (3rd November 2015) - van der Holst, Helena M.; van Uden, Inge W.M.; Tuladhar, Anil M.; de Laat, Karlijn F.; van Norden, Anouk G.W.; Norris, David G.; van Dijk, Ewoud J.; Esselink, Rianne A.J.; Platel, Bram; de Leeuw, Frank-Erik
Abstract : Objective: To investigate the relation between baseline cerebral small vessel disease (SVD) and the risk of incident parkinsonism using different MRI and diffusion tensor imaging (DTI) measures. Methods: In the Radboud University Nijmegen Diffusion Tensor and Magnetic Resonance Cohort (RUN DMC) study, a prospective cohort study, 503 elderly participants with SVD and without parkinsonism were included in 2006. During follow-up (2011–2012), parkinsonism was diagnosed according to UK Brain Bank criteria. Cox regression analysis was used to investigate the association between baseline imaging measures and incident all-cause parkinsonism and vascular parkinsonism (VP). Tract-based spatial statistics analysis was used to identify differences in baseline DTI measures of white matter (WM) tracts between participants with VP and without parkinsonism. Results: Follow-up was available from 501 participants (mean age 65.6 years; mean follow-up duration 5.2 years). Parkinsonism developed in 20 participants; 15 were diagnosed with VP. The 5-year risk of (any) parkinsonism was increased for those with a high white matter hyperintensity (WMH) volume (hazard ratio [HR] 1.8 per SD increase, 95% confidence interval [CI] 1.3–2.4) and a high number of lacunes (HR 1.4 per number increase, 95% CI 1.1–1.8) at baseline. For VP, this risk was also increased by the presence of microbleeds (HR 5.7, 95% CI 1.9–16.8) and a low gray matter volume (HR 0.4 per SD increase, 95% CI 0.2–0.8). Lower fractional anisotropy values in bifrontal WM tracts involved in movement control were observed in participants with VP compared to participants without parkinsonism. Conclusions: SVD at baseline, especially a high WMH volume and a high number of lacunes, is associated with incident parkinsonism. Our findings favor a role of SVD in the etiology of parkinsonism.